ANTI-MICROBIAL EFFECTIVENESS OF LEMON GRASS OIL (CYMBOPOGAN CITRATE) AGAINST AEROBIC AND ANAEROBIC ORGANISMS - S. M., AJJAI; NAIR, POOJA; GRACE, J. R. LILLY; VENNILA, ROSY (International Journal of Current Pharmaceutical Research, 2021)
Objective: To find the antibacterial effectiveness of lemon grass (Cymbopogan citrate) oil against aerobic and anaerobic bacteria. Methods:This is an observational study conducted at Microbiology Clinical laboratory, Department of Microbiology, Saveetha Medical College and Hospital, Chennai. It was done over a period of 3 mo from January to March. The extracts of lemongrass leaves were investigated for its effectiveness against Staphylococcus aureus(S.aureus), Escherichia coli(E.coli) and Clostridium perfringens(C.perfringens) by Disc Diffusion assay. Results:Our study indicates that the extract of lemongrass oil shows antibacterial activity. Among the tested organisms, aerobic organisms were sensitive. Conclusion: This study thus provides insightful knowledge on antibacterial activity that would lead to further development of lemongrass oil for infectious diseases in the future.